Large-scale agent simulation of agent-based models - Poh, Wei Li. (2012)
Agents are a very useful form of modelling and understanding complex natural systems. Agent-based simulations have been applied in many different domains, such as: economics, sociology, psychology, etc. While they offer a very flexible approach to modeling such systems, they often require significant computational resources for execution.